PREFERENSI KEPUTUSAN MUZAKKI MEMBAYAR ZAKAT DI LEMBAGA AMIL ZAKAT MELALUI PEMBAYARAN DIGITAL - Abdillah Khairurrijal; Ajeng Kartika Galuh; M. Jaenudin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Indonesia has great zakat potential, but its realization is not yet commensurate with the existing potential. This research aims to examine four factors influencing the preference for making zakat payments through digital media in zakat institutions. These factors include financial technology (FinTech) knowledge, zakat knowledge, lifestyle, and satisfaction. The focus of this study is on Muzakki at the Lembaga Manajemen Infaq (LMI) in Malang. The data analysis method employed is SEM-PLS (Structural Equation Modelling-Partial Least Square), with path analysis using SmartPLS 4 to test the pattern of relationships between variables. The results indicate that all four factors have a positive relationship with the preference for making zakat payments through digital media at zakat institutions. It is expected that the findings of this research can serve as a reference regarding the preference for using digital media to optimize the collection of zakat funds or enhance community participation in fulfilling zakat payments.